Usefulness of new subtraction algorithm in estimating degree of liver fibrosis by calculating extracellular volume fraction obtained from routine liver CT protocol equilibrium phase data: Preliminary experience - Shinagawa, Yoshinobu; Sakamoto, Keiko; Sato, Keisuke; Ito, Emi; Urakawa, Hiroshi; Yoshimitsu, Kengo (European journal of radiology, 2018)
•Hepatic CT extracellular volume fraction correlates with liver fibrosis grades.•New subtraction algorithm provides best extracellular volume fraction.•Extracellular volume fraction can be obtained from routine clinical CT data.•Further investigation is needed to determine optimal equilibrium phase delay time. To assess whether extracellular volume fraction (ECV) obtained from routine liver CT equilibrium phase data utilizing new subtraction algorithm is useful in estimating the degree of liver fibrosis. Consecutive 41 patients, 21 men and 20 women, with chronic liver diseases who underwent quadri-phase liver CT and MR elastography within 3 months were retrospectively enrolled. Subtraction image of unenhanced from equilibrium phase (240 s) images using conventional and new algorithms were made. We firstly assessed the quality of these subtraction algorithms using patients in whom anatomical misregistration between the two image sets were prominent. Then, ECVs were calculated using both subtraction data sets (ECV-convSub, and ECV-newSub, respectively). ECV were also calculated by traditional manual method (ECV-man). Correlation coefficients of 3 types of ECV were compared using liver stiffness (kPa) as measured by MR elastography and pathologically proven fibrosis grades as reference standards. For eleven patients with prominent anatomical misregistration between the unenhanced and equilibrium phases, new algorithm provided significantly better subtraction images than the conventional one (p = 0.001, Wilcoxon’s signed rank test). As for correlation with liver stiffness, R2 for ECV-man, ECV-convSub, and ECV-newSub, were 0.57, 0.59, and 0.66, respectively (all p < 0.0001, Pearson’s correlation). Histological assessment for fibrosis grades were available in 20 patients, and rho values for these three ECVs were 0.66, 0.61, and 0.71, respectively (all p < 0.01, Spearman’s rank correlation). ECV-newSub showed better correlation to liver stiffness and pathological fibrosis grades than ECV-convSub and ECV-man, which could be a reliable biomarker of liver fibrosis obtained from routine clinical diagnostic imaging data, where equilibrium phase delay time was set at 240 s.